Respon Pertumbuhan Trichoderma brevicompectumIndigenus Gorontalo pada Beberapa Media Limbah Pertanian - Siska Irhamnawati Pulogu; Rida Iswati; Silvana Apriliani; Delvira Isami; Reska Lamatenggo (Politeknik Negeri Lampung., 2026)
Trichoderma brevicompactum indigenous to Gorontalo is a potential biological control agent that plays an important role in plant disease management and agricultural waste utilization. The availability of cost-effective and environmentally friendly growth media is a key factor in supporting the production of fungal inoculum. This study aimed to describe the growth response of Gorontalo indigenous T. brevicompactum on agricultural waste-based media, namely cassava peel extract and coffee peel extract, in comparison with Potato Dextrose Broth (PDB) as a control medium. The study was conducted using a descriptive approach at the Laboratory of Plant Pests and Diseases, Faculty of Agriculture, Universitas Negeri Gorontalo. The observed parameters included changes in the physical properties of the media (temperature, pH, and color), mycelial biomass, relative growth rate (RGR), absolute growth rate (AGR), and conidial density during the incubation period. The results showed that, descriptively, cassava peel extract exhibited a higher tendency in RGR and AGR values than the control medium and coffee peel extract, particularly during the mid-incubation phase. In contrast, coffee peel extract showed a relatively lower growth response, especially at the later incubation stage. Conidial density increased over time in all media, with the highest values observed in the control medium, followed by cassava peel extract and coffee peel extract. Overall, cassava peel and coffee peel wastes have potential as alternative growth media for T. brevicompactum, with cassava peel extract demonstrating a more favorable growth tendency.